Le habous, instrument de protection de la biodiversité ? Le cas du Maroc dans une approche de droit comparé. - Samira Idllalène (Développement Durable et Territoires)
The case of Moroccan law in a comparative law approach. The habous (waqf) is an institution anchored in the culture and the Muslim law. Its environmental feature is not enough exploited any more today while it could mitigate the lack of effectiveness of the modern law. The revival of the patrimonial potential of the habous requires at first to explain its foundations, before analyzing the multiple declensions of this institution in the field of biodiversity.